Herbal Components of a Novel Formula PSORI-CM02 Interdependently Suppress Allograft Rejection and Induce CD8+CD122+PD-1+ Regulatory T Cells - Lu, Chuanjian; Liu, Huazhen; Jin, Xiaowei; Chen, Yuchao; Liang, Chun-Ling; Qiu, Feifei; Dai, Zhenhua (Frontiers in Pharmacology, 2018)
A recipient usually rejects a transplanted organ and thus needs immunosuppressive treatments to prevent rejection. Achieving long-term allograft survival without continuous global immunosuppression is highly desirable in transplantation as long-term immunosuppression causes various side effects. Therefore, it is necessary to search for medicine with potentially less side effects. Traditional Chinese medicine PSORI-CM01 (Yin Xie Ling), a formula with seven natural herbs, has been used to treat patients with psoriasis. Here we investigated a “sharpened” formula, PSORI-CM02 consisting of only five herbs from PSORI-CM01: Curcumae rhizoma, Radix paeoniae rubra, Rhizoma smilacis glabrae, Mume fructus and Sarcandrae herba. We examined whether or not PSORI-CM02 would suppress alloimmunity and found that PSORI-CM02 significantly inhibited murine skin allograft rejection and reduced graft-infiltration of CD3+ T cells. Interestingly, omitting any single herbal component rendered the whole formula ineffective in suppression, indicating that these herbal components exert their effects cooperatively as a whole. Moreover, PSORI-CM02 increased CD8+CD122+PD-1+ Treg frequency with CD4+FoxP3+ Tregs remaining unchanged in recipient mice, whereas CsA reduced CD4+FoxP3+ Treg frequency. PSORI-CM02 also hindered CD11c+ DC maturation posttransplantation. Importantly, PSORI-CM02-induced CD8+CD122+PD-1+ Tregs were more potent in suppression of allograft rejection in Rag-/- mice than control Tregs. On the other hand, PSORI-CM02 suppressed T cell proliferation in vitro and reduced their phosphorylation of P70S6K and P50/P65, suggesting that it inhibits both mTOR and NFκB signaling pathways. It also increased IL-10 production while reducing IFNγ level in the supernatant of activated T cells co-cultured with CD8+CD122+PD-1+ Tregs. Furthermore, HPLC fingerprinting ruled out that PSORI-CM02 contained CsA or rapamycin. PSORI-CM02 also did not cause any illness and toxic injury in recipient mice. Thus, we demonstrate that PSORI-CM02 formula suppresses allograft rejection without toxicity.